Colourful Worlds of Vladimir Maksimov - Dulatova, Khadicha (project baikal, 2015)
The short review of the works by Irkutsk painter Vladimir Gennadievich Maksimov allows the journal readers to look into the roots of the master’s creativity and see his deep mental and spiritual connection with the nature of Pribaikalie. The series of landscapes and genre pictures expresses the author’s fine poetical and musical sense, his rare gift for implementation of fantasy images on a canvas by using paints and a palette knife.
Keywords: co-creation; polyphony; Genius Loci; palette knife; Irkutsk; Pribaikalie